2006
DOI: 10.1007/bf03033355
|View full text |Cite
|
Sign up to set email alerts
|

Implications of co-morbidity for etiology and treatment of neurodegenerative diseases with multifunctional neuroprotective-neurorescue drugs; ladostigil

Abstract: The recent therapeutic approach in which drug candidates are designed to possess diverse pharmacological properties and act on multiple targets has stimulated the development of several multifunction drugs. These include ladostigil (TV3326) [(N-propargyl-(3R) aminoindan-5yl)-ethyl methyl carbamate], which combines the pharmacophore-neuroprotective effects of rasagiline, a selective monoamine oxidase (MAO)-B inhibitor, with the cholinesterase (ChE) inhibitory activity of rivastigmine or iron chelating moiety su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 90 publications
3
25
0
Order By: Relevance
“…Pharmacological studies have demonstrated that MAO inhibitors exert neuroprotective effects in patients with AD (21,52,53) through the following mechanisms: Improvement of cognitive impairment (50,54,55); antioxidant and enhancement of iron chelating activities (56-59); regulation of APP and Aβ expression processing (56,60), involving the activation of certain signaling pathways, including the p42/44 mitogen-activated protein kinase (MAPK) and protein kinase C (PKC) signaling pathways (61); and inhibition of cholinesterase (ChE) activity (62-64).…”
Section: Involvement Of Mao In Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological studies have demonstrated that MAO inhibitors exert neuroprotective effects in patients with AD (21,52,53) through the following mechanisms: Improvement of cognitive impairment (50,54,55); antioxidant and enhancement of iron chelating activities (56-59); regulation of APP and Aβ expression processing (56,60), involving the activation of certain signaling pathways, including the p42/44 mitogen-activated protein kinase (MAPK) and protein kinase C (PKC) signaling pathways (61); and inhibition of cholinesterase (ChE) activity (62-64).…”
Section: Involvement Of Mao In Neurodegenerationmentioning
confidence: 99%
“…It has been established that MAO, a marker of oxidative stress, is linked to the production of reactive oxygen species and other molecules that cause oxidative stress, which results in neuronal damage and neurodegeneration, including AD, indicating that excessive MAO activity contributes to neurodegeneration in AD (62,(111)(112)(113). Molecular biology studies have shown the critical role of Aβ generation through the modulation of APP processing by MAO (60,61,114,115) (Fig. 2).…”
Section: Activated Mao Contributes To the Formation Of Amyloid Plaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ladostigil also has been reported to enhance soluble amyloid precursor protein (APP)-␣ secretion via the protein kinase C-MAP kinasedependent pathway, and to decrease the levels of holo-APP (i.e., actions that favor cell viability). [13][14][15] Thus, ladostigil represents a new drug class that is potentially suitable for the treatment of Alzheimer's disease (AD). Patients with AD require therapies that will delay the progression of the disease, and they may suffer from impaired attention, impaired memory, extrapyramidal disorders, and depression.…”
Section: Rational Molecular Designmentioning
confidence: 99%
“…31 The MTDL approach has been employed by many research groups [32][33][34][35] and has shown success, for example in the case of the compound ladostigil 36 which has reached clinical trials. 37 Exploiting the advantage of conjunctive approach, we designed a series of compounds combining known scaffolds of MAO and ABAD inhibitors to introduce MAO inhibitory activity into frentizole moiety and explore structural inhibitory features of both MAO and ABAD scaffolds. Xie et al observed that the FDA approved drug, frentizole ( Fig.…”
Section: Introductionmentioning
confidence: 99%